RETHINKING INSURANCE DISPUTES - Abdalyan, Ani M. (Assurances et gestion des risques / Insurance and Risk Management, 2003)
All stakeholders in the insurance industry appreciate the critical importance of alternate dispute resolution (“ADR”) to the resolution of insurance disputes. What follows is a practical and in-depth analysis of negotiation, mediation, and arbitration as these dispute resolution methods relate to insurance. The author weaves in confidentiality, privilege, and ethics with a view to enhancing the effectiveness and efficiency of ADR in insurance disputes. This analysis serves as a foundation tool for ADR practitioners in the insurance industry and for future thoughts to follow.